2021
DOI: 10.1016/j.jjcc.2021.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic/bleeding event after short dual-antiplatelet therapy in patients with high bleeding risk: Sub-analysis of the MODEL U-SES study

Abstract: Background: This analysis aimed to evaluate the clinical impact of high bleeding risk (HBR) on adverse events after percutaneous coronary intervention (PCI). Methods:We retrospectively analyzed 1695 patients in the MODEL U-SES study, which was a multicenter, open-label, prospective observational study evaluating safety of 3-month dual antiplatelet therapy (DAPT) after Ultimaster stent (Terumo Corporation, Tokyo, Japan) implantation at 65 sites in Japan. Patients were divided into 2 groups (HBR/Non-HBR) accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Since major bleeding events seem to increase over time as shown in a previous report and our data [11], we believe that all three definitions are equally useful in distinguishing a high bleeding population through long-term periods. While not only bleeding but also ischemic events are related to post-PCI mortality, the diagnostic value for long-term ischemic events in each definition was similar [24][25][26]. We found that each definition could be used similarly for predicting major bleeding and ischemic events.…”
Section: Discussionmentioning
confidence: 73%
“…Since major bleeding events seem to increase over time as shown in a previous report and our data [11], we believe that all three definitions are equally useful in distinguishing a high bleeding population through long-term periods. While not only bleeding but also ischemic events are related to post-PCI mortality, the diagnostic value for long-term ischemic events in each definition was similar [24][25][26]. We found that each definition could be used similarly for predicting major bleeding and ischemic events.…”
Section: Discussionmentioning
confidence: 73%